Kerangka Pikir Tanpa Arah: Kritik atas Lemahnya Fondasi Teoretis dalam Penelitian Pendidikan Modern - Selvi, Nurhayati; Ondeng, Syarifuddin; Rahman, Ulfiani (Program Studi Pendidikan Bahasa dan Sastra Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Islam Makassar, 2026)
This study examines the relationship between theory, conceptual framework, and hypothesis in educational research. The problem raised relates to the still weak ability of researchers to formulate a scientifically integrated and consistent conceptual framework. This research aims to critically examine the practice of using theory in educational research, including Islamic education, and to formulate strategies for strengthening theoretical and conceptual foundations in order to achieve scientific coherence and epistemological accuracy. The method used is a literature study through descriptive analysis of the methodology and educational research literature. The results of the study indicate that the weak integration of theory is caused by a minimal understanding of the function of theory, a lack of systematic development of the conceptual framework, and the formulation of hypotheses that are not derived from theoretical argumentation. This study emphasizes the importance of positioning theory, conceptual framework, and hypothesis as a functionally interrelated unit. In the context of Islamic education, strengthening theoretical foundations requires a reflective integration between the naqli and aqli approaches so that research is not only methodologically valid but also epistemologically authentic. These findings provide a conceptual contribution in the form of a framework for strengthening theoretical foundations that can serve as a reference in improving the quality of educational research.